“Triple Ps” in infrastructure development and economic growth in Sub-Saharan Africa - Wessel, De Wet (Graduate School of Business (GSB), 2024)
The study focused on the impact that public private partnerships (PPP) has had on the economies of sub-Saharan African countries. A quantitative approach was decided on to extend the limited empirical studies performed relating to the impact that PPPs have on the economies of sub-Saharan Africa. The dissertation has covered annual data extracted from the Work Bank PPI database covering 47 of the 55 African states between 1995 and 2015. The analysis was designed and performed to test the impact that each of the independent variables: 1) the total PPP investment, 2) the PPP investments per type and 3) the PPP Investment per sector had on economic growth measured and presented by the Gross Domestic Product (GDC) using the System Generalised Method of Moments estimation technique. From the panel data analysis, the study could not find a significant effect of total PPPs on economic growth. However, the disaggregation analysis shows that both Brownfield and Management and Lease contract types of PPP had a positive and significant effect on economic growth. This is in line with the theoretical suggestion that the public sector could improve the impact that infrastructure investments have on economic growth by improving operational efficiency and innovation. In terms of the difference in the results per sector, it does appear that PPPs in water and sewerage have a stronger effect on economic growth compared with PPP investments in other sectors. In addition, a positive effect of PPP in the transport sector on economic growth was also found. Although the result of the analysis does not point to conclusive evidence of a causal relationship between PPP and economic growth, the paper does provide necessary context to the growing criticism of PPP, and points to further research that should be instituted to understand the key performance criteria for PPPs and for discussions relating to the subject to be re-ignited.